The Effect of Core Stability Training on Fundamental Skills of Children with Visual Impairments - Fatemehsadat Hosseini; Omid Farjollahi (University of Tehran, 2018)
Visual impairments as an individual constraint can lead to the lack of adequate visual perception and overshadow children's all developmental aspects. Therefore, the aim of the present study was to investigate the effect of a course of core stability training on fundamental skills in visually impaired boys. 30 visually impaired children (age range: 5-7 years) were selected by convenience sampling method. After the Ulrich pretest, they were randomly divided into two groups: the core stability training group and the ordinary daily activities. The experimental group participated in the core stability training for 16 sessions, each session 45 minutes. The control group carried out their daily activities. The results of mixed analysis of variance 2 × 2 and Bonferroni post hoc test indicated a significant difference in scores between the two groups so that the subjects of the experimental group outperformed the control group in all locomotors subscales (P<0.05). In general, the results of the study suggest core stability training as a suitable training model to promote fundamental motor skills in children with visual impairment because of increased levels of motivation and enjoyment of physical activity, the development of the children's physical self-concept and enhancement of abdominal and back muscles performance